Digitizing AJN - &NA (AJN, American Journal of Nursing, 2006)
Pediatric fractures are a common reason for ED visits, yet distinguishing accidental injuries from those caused by child physical abuse (CPA) remains an important and complex clinical challenge. This article clarifies common misconceptions, such as that all spiral fractures are inherently suspicious, by situating them within the broader evidence base related to pediatric orthopedic injury. Delineating fracture types and circumstances with high, moderate, and low specificity for CPA can help the nurse to evaluate each injury within the context of the child's developmental stage, reported cause, and associated findings. Key nursing responsibilities include comprehensive history taking, thorough physical assessment, meticulous documentation, and adherence to mandated reporting laws when CPA is suspected. By deepening nurses' understanding of orthopedic injury patterns and red flags for CPA, this article aims to avoid misassignment of child abuse in cases of accidental spiral fractures and to enhance accurate assignment of child abuse.